Is peer support beneficial for individuals with borderline personality disorder? Exploring its potential and challenges – a scoping review - Dufour, Anne-Sophie; Nadeau, Laurie; Cailhol, Lionel (Frontiers in Psychiatry, 2025)
BackgroundBorderline Personality Disorder (BPD) is associated with profound emotional dysregulation, interpersonal difficulties, and a heightened risk of suicide. Although psychotherapy remains the first-line treatment, systemic limitations such as resource shortages and high dropout rates necessitate exploration of alternative or complementary interventions. In this context, peer support, defined as assistance provided by individuals with lived experience of mental health challenges, has gained interest as a promising complement or alternative to conventional care. Despite its growing use across mental health contexts, its relevance, effectiveness, and limitations remain poorly understood for individuals with BPD.ObjectiveThis scoping review aims to synthesize the current literature on peer support interventions for individuals with BPD, focusing on their benefits, risks, and implementation challenges.MethodsFollowing the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR guidelines, a comprehensive search was conducted across six databases (Medline, PsycINFO, EMBASE, Cochrane Library, CINAHL, and Google Scholar) and grey literature sources. The inclusion criteria were defined using the Population–Concept–Context (PCC) framework. Eleven studies published between 2019 and 2025 were included. Data extraction focused on study design, participant characteristics, intervention content and structure, outcomes, and implementation challenges.ResultsPeer support interventions varied from structured and manualized programs to flexible and community-based formats. Reported benefits included improved emotion regulation, reduced isolation, enhanced empowerment, and increased hope. Peer workers also reported personal growth and a strengthened sense of purpose. However, challenges such as emotional exhaustion, role ambiguity, inadequate supervision, and limited engagement in online settings were frequently noted. Only a few studies included quantitative measures of symptom change, and methodological heterogeneity limited cross-study comparisons.ConclusionsPeer support interventions show promising psychosocial benefits for individuals with BPD, particularly in domains related to relational connectedness, emotional coping, and subjective recovery. However, evidence remains limited by a lack of standardized models and rigorous evaluation. Future studies should employ mixed-method and controlled designs to better assess clinical outcomes and ensure safe, effective, and sustainable peer-led programs for this population.